Mediações visíveis na cidade: olhares sobre o racismo em Belém do Pará - PINHEIRO, Tainara Lúcia (Universidade Federal do Pará, 2021)
In Belém do Pará the assumption that we are a morena city for a moreno people prevails, with increasing illocutionary strength. This assumption, the result of a common sense that seeks to classify/categorize the ethno-racial mixtures produced, since the colonial context, has increasingly become a local discursive construction to accommodate the diverse and often opposite interpretations about our identity. The analysis proposed here, allows us to reflect on the construct of morenidade, this violent miscegenated identification that for a long time has been presented as a central cultural feature of the city's identity, as a local discursive construction, a representation of strong sensoryvisual appeal, whose historical-cultural interpretation is, at the same time, the result of struggle and negotiation between groups and social classes, of resistance and the imposition of forces in struggle for the classification of alterities produced alongside Amazonian ethnic racial miscegenations.